Fungal CNS Infections in Africa: The Neuroimmunology of Cryptococcal Meningitis - Mohamed, Sally H.; Nyazika, Tinashe K.; Ssebambulidde, Kenneth; Lionakis, Michail S.; Meya, David B.; Drummond, Rebecca A. (Frontiers in Immunology, 2022)
Cryptococcal meningitis (CM) is the leading cause of central nervous system (CNS) fungal infections in humans, with the majority of cases reported from the African continent. This is partly due to the high burden of HIV infection in the region and reduced access to standard-of-care including optimal sterilising antifungal drug treatments. As such, CM is responsible for 10-15% of all HIV-related mortality, with a large proportion being preventable. Immunity to the causative agent of CM, Cryptococcus neoformans, is only partially understood. IFN producing CD4+ T-cells are required for the activation of myeloid cells, especially macrophages, to enable fungal killing and clearance. However, macrophages may also act as a reservoir of the fungal yeast cells, shielding them from host immune detection thus promoting latent infection or persistent chronic inflammation. In this chapter, we review the epidemiology and pathogenesis of CNS fungal infections in Africa, with a major focus on CM, and the antifungal immune pathways operating to protect against C. neoformans infection. We also highlight the areas of research and policy that require prioritisation to help reduce the burden of CNS fungal diseases in Africa.